2023
DOI: 10.1111/apa.16843
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paediatric intensive care due to congenital heart defects on maternal mental health

Abstract: Aim: Successful mother-child-bonding is a fundamental step for a healthy development of the child. Different factors like postpartum depression can hinder the bonding process. This study aimed to investigate how intensive care treatment due to congenital heart diseases of the infant alters bonding and how mothers cope with the situation.Methods: Validated questionnaires were used to analyse postpartum depression, mother-child bonding, stress factors and coping strategies for mothers at a paediatric intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…The predictive model of the heart problem and treatment dimension shows a negative effect of the following independent variables: being a 5-to 7-year-old patient with a ToF conduit or UVH diagnosis, with mothers suffering from mild and moderate depression levels. Some studies (Brandt et al, 2023;Erbas et al, 2023) have observed that mothers of children treated at an intensive care unit due to congenital heart disease are at increased risk for the development of depression and di culties in different aspects of postpartum bonding.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive model of the heart problem and treatment dimension shows a negative effect of the following independent variables: being a 5-to 7-year-old patient with a ToF conduit or UVH diagnosis, with mothers suffering from mild and moderate depression levels. Some studies (Brandt et al, 2023;Erbas et al, 2023) have observed that mothers of children treated at an intensive care unit due to congenital heart disease are at increased risk for the development of depression and di culties in different aspects of postpartum bonding.…”
Section: Discussionmentioning
confidence: 99%